2011
DOI: 10.1007/s10620-011-1593-2
|View full text |Cite
|
Sign up to set email alerts
|

Management of Common Bile Duct Stones in Cirrhotic Patients with Coagulopathy: A Comparison of Supra-Papillary Puncture and Standard Cannulation Technique

Abstract: SPP is a safe and effective technique for the management of common bile duct stones in decompensated cirrhotic patients. Conditional to the willingness-to-pay and to the local ERCP-related costs, SPP is also a cost-effective alternative to the SC methods. SPP is associated with a lower rate of complications but larger studies to validate these findings are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Similarly, increased rates of PEP with EST were seen by Adler et al[ 16 ]. Artifon et al[ 21 ] showed that the risk of PEP was decreased with supra-papillary technique (0%) in comparison with standard cannulation technique (4.8%). Park et al[ 18 ] suggested lower rates of PEP with endoscopic papillary balloon dilation in comparison to EST, but the results did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, increased rates of PEP with EST were seen by Adler et al[ 16 ]. Artifon et al[ 21 ] showed that the risk of PEP was decreased with supra-papillary technique (0%) in comparison with standard cannulation technique (4.8%). Park et al[ 18 ] suggested lower rates of PEP with endoscopic papillary balloon dilation in comparison to EST, but the results did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Often these explorations were not therapeutic as the jaundice was presumably related to the decompensation of chronic liver disease and not obstruction 6,8,18–22 . This type of scenario has become uncommon since the accuracy of imaging 85,86 and efficacy of endoscopic intervention 87,88 have improved and percutaneous biliary interventions have become available 83,89,90 . More generally, the death rate from chronic liver disease has changed substantially coincident with the introduction of LC 91,92 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years several studies on ERCP in liver cirrhosis have been conducted . A major pitfall of these studies is that they defined decompensation or progression of liver cirrhosis using the Child–Turcotte–Pugh classification, which might have been biased by obstructive jaundice and acute inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%